Genome-Wide Identification and Comparative Profiling of MicroRNAs Reveal Flavonoid Biosynthesis in Two Contrasting Flower Color Cultivars of Tree Peony - Luo, Xiaoning; Luo, Sha; Fu, Yaqi; Kong, Chen; Wang, Kai; Sun, Daoyang; Li, Mengchen; Yan, Zhenguo; Shi, Qianqian; Zhang, Yanlong (Frontiers in Plant Science, 2022)
MicroRNA (miRNA)-mediated gene regulation is involved in various physiological processes in plants. Flower color is one of the vital ornamental traits of tree peony (Paeonia suffruticosa Andr.). However, the yellow-flowered tree peony cultivars are particularly rare. To elucidate the miRNA-mediated gene regulatory mechanism underlying yellow pigmentation in tree peony, we combined pigment assessment, miRNA identification, expression analysis, and gene functional verification in two contrasting flower color cultivars ‘High Noon’ and ‘Roufurong’. Flavones/flavonols and anthocyanins were found to be the main contributors to the coloration of ‘High Noon’ and ‘Roufurong’ petals, respectively. Subsequently, miRNA analysis based on available genome data identified 9 differentially expressed miRNAs and 12 relevant target genes implicated in flavonoid biosynthesis. Their dynamic expression patterns determined the key role of mdm-miR156b-PsSPL2 module in yellow pigmentation of tree peony flowers. The sequence analysis and subcellular localization validated that PsSPL2 might function as a nuclear-localized transcription factor. Overexpression of PsSPL2 in tobacco resulted in a decrease of anthocyanin content and down-regulation of NtF3’H and NtDFR transcripts. PsSPL2-silenced petals exhibited lighter yellow color, and the contents of THC, Ap, and Ch decreased significantly. Meanwhile, expression levels of PsCHS, PsCHI, and PsF3H were significantly decreased in the petals with PsSPL2 silencing, while those of PsF3’H and PsDFR were remarkably increased. This study offers a novel insight into yellow pigmentation-related miRNA regulation network in tree peony, and further provides the valuable information on physiological changes during yellow coloring process of tree peony.